Family Education As An Adult Learning Ecosystem: Mapping Coping Strategies And Protective Factors To Strengthen Family Resilience - Nining Purwaningsih; Ahmad Fauzi (Universitas Pahlawan Tuanku Tambusai, 2026)
Family resilience has become an important issue as families face increasingly complex challenges, including parenting difficulties, economic pressures, work-family demands, interpersonal conflicts, and psychological stress. This study aims to explore how adults develop family resilience through coping strategies and protective factors within the context of family education as an informal adult learning process. This study employed a descriptive qualitative approach involving ten adults with caregiving responsibilities in Serang, Banten, Indonesia. Data were collected through open-ended questionnaires, observations, and documentation, and analyzed using thematic analysis. The findings revealed four main themes related to family resilience development: family stressors, daily motivators, coping strategies, and protective factors. Family stressors experienced by participants became starting points for reflection and learning, enabling adults to develop adaptive coping strategies, including problem-focused coping, emotion-focused coping, and spiritual coping. Furthermore, family support, social support, spirituality, optimism, and self-motivation emerged as essential protective factors that strengthened resilience. This study proposes a dynamic pathway of family resilience development: Family Stressors → Reflection and Learning → Coping Strategies → Protective Factors → Resilience Development. The findings indicate that family resilience is not merely the ability to endure adversity but a continuous learning process in which adults transform life experiences into adaptive competencies. This study contributes to family education research by highlighting the role of informal adult learning processes in strengthening family resilience and providing implications for developing resilience-oriented family education programs.